2015
DOI: 10.1038/ng.3242
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of more than 120,000 individuals identifies 15 new susceptibility loci for breast cancer

Abstract: Genome wide association studies (GWAS) and large scale replication studies have identified common variants in 79 loci associated with breast cancer, explaining ~14% of the familial risk of the disease. To identify new susceptibility loci, we performed a meta-analysis of 11 GWAS comprising of 15,748 breast cancer cases and 18,084 controls, and 46,785 cases and 42,892 controls from 41 studies genotyped on a 200K custom array (iCOGS). Analyses were restricted to women of European ancestry. Genotypes for more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
531
0
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 547 publications
(566 citation statements)
references
References 38 publications
10
531
0
18
Order By: Relevance
“…Rather, at the germline level, several intronic KCNN4 single nucleotide polymorphisms (SNPs) have been shown to alter women's breast cancer risk in general and particularly of ER‐positive breast cancer. The observed effect size is small, but is of genome‐wide significance ( P  < 10 −6 ) (Lo et al ., 2016; Michailidou et al ., 2015). How the genetic variants affect SK4 expression in normal breast tissue and breast tumour is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, at the germline level, several intronic KCNN4 single nucleotide polymorphisms (SNPs) have been shown to alter women's breast cancer risk in general and particularly of ER‐positive breast cancer. The observed effect size is small, but is of genome‐wide significance ( P  < 10 −6 ) (Lo et al ., 2016; Michailidou et al ., 2015). How the genetic variants affect SK4 expression in normal breast tissue and breast tumour is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because the majority of identified SNPs fall outside of protein-coding regions, 3 a major challenge is determining how genetic variation in these regions contributes to disease. Several studies have shown that GWAS SNPs are enriched in regulatory regions and can influence the expression of nearby protein-coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…7 Other high-risk susceptibility genes such as TP53, PTEN, CDH1, STK11 and PALB2 have been identified, as well as a number of intermediate-risk genes such as ATM, CHEK2, NBN and NF1, and close to 100 low-risk alleles. 8,9 Despite this, all in all, only about 50% of the excess risk is explained today. Evidence is starting to emerge that some breast cancer genes may harbour different types of variants with inversely correlated cancer risks and allele frequencies: for example, BRCA2 and TP53, on top of a myriad of high-risk rare variants, also harbour more frequent variants associated with lower breast cancer risk, p.K3326X 10 and p.R337H, 11 respectively.…”
Section: Introductionmentioning
confidence: 99%